Retrospective Comparative Analysis of Clinical and Imaging Features of Craniocervical Artery Dissection: Spontaneous CAD vs. Minor Traumatic CAD - Xu, Dan; Wu, Yongjun; Li, Jingjing; Xing, Shihui; Chen, Hongbing; Chen, Xinran; Tan, Yan; Zhou, Kun; Zhang, Guofen; Zhang, Jian (Frontiers in Neurology, 2022)
Background and Objectives: Cranio-cervical artery dissection (CAD) is the most common cause of ischemic stroke in young adults. The aetiologies of CAD can be classified into three types including spontaneous (sCAD), minor traumatic (mt CAD) and genetic origin. Recent studies indicated that clinical presentations and imaging features could guide management and inform prognosis. This retrospective analysis sought to compare the clinical and imaging features of sCAD versus mtCAD in providing evidence-based advice on medical treatment, functional rehabilitation, secondary stroke prevention and prognosis, ultimately formulating clinical guideline in managing CAD. Methods: 148 patients with CAD were identified from medical records database, and subdivided into sCAD and mtCAD based on the clinical presentations and imaging features. A retrospective comparative analysis was performed according to their clinical presentations and imaging features. Results: mtCAD patients are significantly younger than sCAD with 120 cases of sCAD average aged 43.61+/-12.75, while 28 cases of mtCAD average aged 35.68+/-14.54. mtCAD patients had more cases of neck pain compared to sCAD. mtCAD patients had more cases of CAD at extracranial location compared to sCAD. mtCAD patients had more cases of multiple site dissection compared to sCAD. Double lumen and intramural haematoma are the most common imaging findings with mtCAD patients having statistical significantly more cases of intramural haematoma and long tapering stenosis. Conclusion: mtCAD patients presented at much younger age with symptoms of neck pain compared to sCAD. mtCAD patients predominantly presented at extracranial sites with more prominent features of multiple site dissection, intramural haematoma and long tapering stenosis. These clinical and imaging features can translate into clinical practice guidelines for CAD patients to improve the optimal functional outcome and reduce both morbidity and mortality.